1997
DOI: 10.1016/s1010-5182(97)80078-9
|View full text |Cite
|
Sign up to set email alerts
|

Tooth eruption through autogenous and xenogenous bone transplants: a histological and radiographic evaluation in beagle dogs

Abstract: S U M M A R Y . The effect of implanting autogenous and xenogenous (Bio-Oss) bone transplants into metabolically active sites within beagle dog mandibles during permanent premolar tooth eruption was examined. Ten 14-weekold beagles were used. Before commencing the radiographic experiments, metal bone markers were placed in the caudal margin of the mandible at the age of 10 weeks. The deciduous first and third molar teeth were extracted and their sockets over the permanent second and fourth premolars were impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
3
8
0
1
Order By: Relevance
“…The obtained results in addition to confirming the wellknown non-biodegradability of HA demonstrated that the observed and quantified general biodegradation behavior of Skelite TM and Bio-Oss® is in agreement with that reported in (Komlev et al, 2006;Merkx et al, 1997;Merkx et al, 1999;Rumpel et al, 2006). Nevertheless, the promising and effective 3D microCT registration procedure employed in the present work, together with the adoption of a large number of implantation times, introduces an appreciable increase in the existing information with regard to biodegradation of bone mimetic scaffolds and of Si-TCP based scaffolds in particular.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The obtained results in addition to confirming the wellknown non-biodegradability of HA demonstrated that the observed and quantified general biodegradation behavior of Skelite TM and Bio-Oss® is in agreement with that reported in (Komlev et al, 2006;Merkx et al, 1997;Merkx et al, 1999;Rumpel et al, 2006). Nevertheless, the promising and effective 3D microCT registration procedure employed in the present work, together with the adoption of a large number of implantation times, introduces an appreciable increase in the existing information with regard to biodegradation of bone mimetic scaffolds and of Si-TCP based scaffolds in particular.…”
Section: Resultssupporting
confidence: 91%
“…This result correlates with the common knowledge based on literature data that HA is a non-biodegradable material. Moreover, the observed and quantified general biodegradation behavior of Skelite TM and Bio-Oss® according to the present work were in agreement with previously reported data (Komlev et al, 2006;Merkx et al, 1997;Merkx et al, 1999;Rumpel et al, 2006).…”
Section: Vs Komlev Et Al Biodegradation Of Porous Calcium Phosphate supporting
confidence: 93%
See 1 more Smart Citation
“…Da Silva et al., showed in a dog model that regeneration with BB and then OTM led to augmented osseous tissue . Merkx et al., in a dog model provided similar results as the current study, showing translocation of BB particles due to tooth movement . Yang et al., showed similar results in a rat femur defect model and provided evidence that BB are not resorbed despite significantly increased numbers of OCS and elevated expression of RANKL, specifically around the particle surface .…”
Section: Discussionsupporting
confidence: 83%
“…Several studies 14,19,20,25 demonstrated that allogenic and xenogenic bone grafts, including DBB, had no inhibitory effect on tooth eruption or orthodontic tooth movement in vivo. A case report demonstrated the successful tooth movement, by orthodontic force, through the alveolar cleft region 6 months after grafting with a mix of decalcified freeze-dried bone allograft and a granular bioactive glass graft material in the ratio 1:1 30 .…”
Section: Discussionmentioning
confidence: 99%